Creating Value by Differentiation: The Case of ALDI’s Sustainability Management (Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024, 2024)
In this case study, we examine the management and the effects of sustainable practices on value creation through differentiation in the discount retailer industry. Existing research on sustainability management focuses more on its impact on value creation through cost reduction or efficiency gains. International discount retailers are evolving and growing by adapting to the global business environment's economic, demographic and technological trends. Their types of sustainable practices and the approaches to their management are gaining recognition among consumers. Using ALDI's good practice, we examine the role of strategic and operational planning, the types of sustainable practices, and their effects on creating corporate value through differentiation. The case study reveals the role of analyzing the primary and supporting activities of a company's value chain in terms of opportunities to improve sustainability management and to find new sustainable practices, focusing on those that create value for the company through differentiation or innovation. It also raises awareness of the importance of sustainable consumption and the possibilities to support it.